Studi Komparasi Software berbasis GUI dan CLI Terhadap Pengukuran Kualitas Throughput Jaringan Nirkabel IEEE 802.11ac - Saputro, Vian Ardiyansyah; Arief, Yanuar Zulardiansyah (Jurnal Komtika (Komputasi dan Informatika), 2024)
One indicator of wireless network performance is throughput quality where the measurement of throughput quality itself has the aim of knowing the quality of service of a network and a picture of the behavior of the network. In measuring the quality of service of a network, supporting software is needed that can be used to measure the value of the quality of throughput. One of the software that can be used is graphical user interface-based software, namely JPERF, and command-line-based software, namely IPERF version 3. This study aims to compare and analyze two Command Line (CLI) based software using iperf version 3 and Graphical User Interface (GUI) based software using jperf which can produce the highest quality of TCP and UDP network throughput. The test results show that the use of JPERF software produces a higher throughput value when measuring throughput quality using the TCP protocol where the largest difference produced is 5 Mbps when sending 384 KB data packets while the throughput quality measurement using the UDP protocol iperf software version 3 produces a higher throughput value where there is the largest difference generated by 22 Mbps when sending 128 KB packets.